Media exposure, perception, attitudes, and use. The philosophy of sufficiency economy. Of youth in Bangkok - Kaewpremkusol, Apinya (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this research were to study 1. the behavior of secondary school students in Bangkok in terms of exposure to media and messages regarding the Sufficiency Economy Philosophy; 2. their awareness of principles of the Sufficiency Economy Philosophy; 3. their attitudes towards the Sufficiency Economy Philosophy; 4. their utilization of principles of the Sufficiency Economy Philosophy; and 5. the relationship between media exposure, attitude and utilization With the philosophy of sufficiency economy of secondary school students in Bangkok. This was a quantitative research. The sample population was 420 secondary school students in Bangkok, chosen through multi-level sampling. Data were collected using a questionnaire and analyzed using percentage, mean, standard deviation and Pearson’s correlated coefficient. The results showed that 1. overall, the samples were exposed to media coverage on the Sufficiency Economy Philosophy at a high level, mainly through television and interpersonal communication the form of family members. 2. Most of the samples were aware of the principle of Sufficing Economy Philosophy at the highest level. 3. Overall, the samples had a positive attitude towards the Sufficiency Economy Philosophy at a high level. 4. Overall, the samples utilized the principles of the Sufficiency Economy Philosophy at a high level. 5. The relationship between media exposure, attitude and utilization from the sufficiency economy philosophy Found that the attitude towards the sufficiency economy philosophy of youth in Bangkok Will have a relationship with receiving personal media (r=0.15) and while the utilization of the sufficiency economy philosophy of youth in Bangkok is related to personal media (r=0.15) and mass media (r=0.12) respectively. While the relationship between media exposure, the research results show that there is a relationship between the media. And specialized media (r=0.58), specialized media and personal media (r=0.54) and mass media and personal media (r=0.35) respectively and found the relationship between Attitude and utilization from sufficiency economy philosophy (r=0.62) Article history : Received 11 January 2019 Revised 28 January 2019 Accepted 30 January 2019 SIMILARITY INDEX = 4.86